2018
DOI: 10.1007/s00261-018-1599-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of diffusion-weighted MR imaging in the diagnosis of placenta accreta spectrum abnormality

Abstract: With the current imaging technique, addition of DWI sequence to the traditional T2W images cannot be shown to significantly increase the accuracy or reader confidence for diagnosis of placenta accreta spectrum abnormality. However, DWI does improve identification of abnormalities in the placental-myometrial interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In contrast to ultrasound, MRI can provide versatile contrast that may provide additional information about the placenta structure and function to assist the diagnosis of PAS disorders. [32][33][34] Bao et al recently investigated the diagnostic value of intravoxel incoherent motion (IVIM) for PAS disorders with accreta lesions and showed that the pseudo-diffusion fraction could predict PAS disorders with an accuracy of 85.7%. 35 Sun et al used textural features and automated machine learning to identify suspicious PAS disorders based on anatomical MRI and achieved sensitivity, specificity, and accuracy of 100%, 88.5%, and 95.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ultrasound, MRI can provide versatile contrast that may provide additional information about the placenta structure and function to assist the diagnosis of PAS disorders. [32][33][34] Bao et al recently investigated the diagnostic value of intravoxel incoherent motion (IVIM) for PAS disorders with accreta lesions and showed that the pseudo-diffusion fraction could predict PAS disorders with an accuracy of 85.7%. 35 Sun et al used textural features and automated machine learning to identify suspicious PAS disorders based on anatomical MRI and achieved sensitivity, specificity, and accuracy of 100%, 88.5%, and 95.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to a recent study, the diagnostic accuracy of ultrasound in predicting PAS disorders was 79.71% in the third trimester 16 while anatomical MRI showed an accuracy of 82%, 15 and MRI is essential for pregnant women with obesity, over‐sized fetus, and oligohydramnios. In contrast to ultrasound, MRI can provide versatile contrast that may provide additional information about the placenta structure and function to assist the diagnosis of PAS disorders 32–34 . Bao et al recently investigated the diagnostic value of intravoxel incoherent motion (IVIM) for PAS disorders with accreta lesions and showed that the pseudo‐diffusion fraction could predict PAS disorders with an accuracy of 85.7% 35 .…”
Section: Discussionmentioning
confidence: 99%
“…dMRI is increasingly part of clinical MRI exams for assessing fetal brain development and injury 57,58,59 . Diffusion imaging has also been included in the assessment of invasive placentation in clinical settings 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…US often the primary imaging tool for evaluating women at risk for PA, such as those presenting with placenta previa and prior cesarean or uterine surgery, whereas MRI is used to con rm US diagnosis and delineate the depth and topography of placental invasion, which may signi cantly affect maternal outcomes and in uence surgical approach [24].US may be limited in detecting more severe placental penetration, especially in assessing the extent of extrauterine involvement of the placenta.In terms of evaluating the degree of invasiveness, MRI outperforms US due to its better inherent contrast.In addition, although the lower uterine segment is the most common site of PA and can usually be evaluated with a high-frequency ultrasonic probe because of its relatively super cial location in pregnancy, other locations of PA may be more di cult to identify by US.When PA is located far from the probe, such as posterior accreta or when the patient is obese, the resolution obtained will not be as good as the former.In this case, US is di cult to identify PA. On MRI, the location of PA abnormality and the patient's body size do not affect the resolution or image quality. In contrast to ultrasound, MRI can provide versatile contrast and may provide additional information about placental structure and function to assist in the diagnosis of PA [25,26]. Sun et al [27].…”
Section: The Recently Released Society Of Abdominal Radiology and Eur...mentioning
confidence: 99%